Component structure of women role in goat rearing - TYAGI, K K; PATEL, M D; SORATHIYA, L M; FULSOUNDAR, A B (The Indian Journal of Animal Sciences, 2013)
The component structure of 25 Likert-type variables measuring different aspects of role of women in goat rearing was investigated using principal components analysis (PCA) with varimax orthogonal rotation. The respondents were 225 goat farmers from 6 clusters adopted under All India Coordinated Research Project on Goat improvement (AICRPG) - Surti Field Unit. Finally 13 Likert-type variables were retained after stepwise exclusion of inappropriate variables from analysis. The Kaiser–Meyer–Olkin measure verified good sampling adequacy for the analysis, KMO = 0.847. Bartlett’s test of sphericity χ² (78) = 1878.40, indicated that correlation between items were sufficiently large for PCA. On the basis of parallel analysis and Kaiser’s criterion, a 2-component structure was found, from which 2 subscales (outdoor roles and indoor roles) with reliabilities of 0.872 and 0.876 explaining 62.01% of the variance were extracted using PCA. Present study elucidated social perceived agreement on outdoor and indoor roles of women in goat rearing as 2 major principle components. Furthermore baseline information on retained and excluded variables by PCA and Reliability statistics will foster future studies to understand role of women in goat rearing more closely